Penerapan Autoregressive Distributed Lag (ARDL) Dalam Memodelkan Pengaruh Lama Sekolah Dan Tingkat Pengangguran Terbuka Terhadap Kemiskinan di Kota Manado - Eka Elencya Trisilia Laloan; Nelson Nainggolan; Djoni Hatidja (Sam Ratulangi University, 2023)
The increase in poverty rates in Manado City, North Sulawesi, is influenced by various factors such as the average length of schooling and the open unemployment rate. This study aims to determine a model and to determine whether the average length of schooling and the open unemployment rate can affect the poverty rate in Manado City from previous time periods using the autoregressive distributed lag (ARDL) model. The data used in this study are secondary data, namely the percentage of poverty rates, average length of schooling, and the percentage of open unemployment rates taken from the Central Bureau of Statistics (BPS) of Manado City, North Sulawesi Province, from the annual period starting from 2003-2021. The results showed that the best model offered by Akaike Information Criteria (AIC) was ARDL (2,2,2) with the smallest AIC value of -0.36 with the model equation with the results that both independent variables, average length of schooling and open unemployment rate, can affect poverty in Manado City.